Etnobotany of Traditional Medicine Plants in the Wawo District, Bima Regency in 2022 - Sri Wahyuningsih; Abdul Syukur; Khairuddin Khairuddin (Jurnal Biologi Tropis, 2022)
Ethnobotany is the study of the traditional use of various kinds of plants by rural communities. Ethnobotany has a very important role to understand the relationship between people and plants. This study aims to determine the number of species medicinal plants and how to use traditional medicinal plants in Wawo distrrict, Bima Regency. This research is descriptive exploratory. Data collection techniques by means of interviews, observation, documentation, and experience. Determining the initial information in this study was carried out by purposive sampling method continued with the snowball sampling method until the data was saturated. Data analysis uses qualitative and quantitative analysis. We documented 83 species belonging to 37 families. The most abundant families are Zingiberaceae (13 species), and Fabaceae (6 species). There are 8 ways to use it, namely that is, by drinking without boiling (18%), boiled before drinking (40%), smeared (20%), dripped (5%), rubbed (8%), blown (3%), gargle (3%), sprayed (3%), the method of utilizing medicinal plants which is most often used by the people of In the Wawo district by boiling before drinking with the highest percentage, which is 40%. The percentages of medicinal plant diversity based on habitus were 55% trees, 6% lianas, 12% small trees, and 25% herbs. There is a need for written documentation regarding knowledge about the use of medicinal plants in In the Wawo Disrict and can be passed on to the younger generation, as well as the need for bioactive research so that traditional use by the community can be scientifically proven.